Peran Sertifikasi BNSP dan Penjaminan Mutu Internal terhadap Reputasi Startup Campus sebagai Lembaga Pelatihan Digital - Ani Nuraeni (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
The rapid development of digital technology in Indonesia has created an urgent need for skilled digital talent. Formal schools often find it difficult to adapt their curricula to the dynamics of the industry, so non-formal training institutions such as Startup Campus have emerged as a solution. Startup Campus, which collaborates with the Kampus Merdeka program and is registered as an official Vocational Training Institution (LPK) by the National Professional Certification Agency (BNSP), serves to bridge the skills gap between education and industry. This study aims to analyze how BNSP certification builds the legitimacy of the Startup Campus training program as well as the internal quality standards and quality communication strategies used. Using a qualitative descriptive approach, data was collected from public documents and promotional materials. The results show that the combination of BNSP certification as an external quality assurance and the implementation of internal quality standards such as industry-based curricula, instructor qualifications, and effective learning methods, enhances the reputation and trustworthiness of the institution among prospective participants. Clear communication about quality, including information about certification and graduate experiences, greatly influences the perceptions of prospective industry partners. These findings highlight the importance of communication strategies in building the reputation of digital training institutions and contribute to the literature on non-formal education quality management in Indonesia. Further research is recommended to involve primary data in order to explore the effectiveness of reciprocal communication strategies in greater depth.